Influence of artificial aging in marginal adaptation of mixed class V cavities - Tonetto, Mateus Rodrigues; Bandéca, Matheus Coelho; Barud, H́lida Gomes de Oliveira; Pinto, Shelon Cristina Souza; Lima, Darlon Martins; Borges, Alvaro Henrique; Campos, Edson Alves de [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP] (Jaypee Brothers Medical Publishing, 2013)
The aim of this study was to investigate whether the artificial aging by thermal cycling had influenced the marginal adaptation of class V restorations with/without chlorhexidine application in the bond process. Twelve intact human third molars were used. Class V cavity preparations were performed on the buccal surface and the teeth received 35% phosphoric acid-etching procedure (Ultradent Products Inc., South Jordan, Utah, USA). Subsequently, the samples were divided in two groups: Untreated acid-etched dentin and chlorhexidine application as an adjunct in the bond process. The adhesive Single Bond 2 (3M ESPE, St. Paul, MN, USA) was used after 2% chlorhexidine application, and the restorations were performed with FiltekTM Z350 XT (3M ESPE) composite resin. The specimens were submitted to artificial aging by thermal cycling with 3,000 cycles. Analyzes were performed on scanning electron microscopy using replicas of marginal adaptation in percentage of continuous margin before and after the artificial aging. The data were analyzed by paired test and the results showed statistically significant differences in the percentage of continuous margin with/without chlorhexidine treatment before and after thermal cycling. This study concluded that the artificial aging by thermal cycling influenced the marginal adaptation of mixed class V composite restorations.
Keywords: Artificial aging; Chlorhexidine; Dental marginal adaptation